Law as Change: Engaging with the Life and Scholarship of Adrian Bradbrook - Babie, Paul; Leadbeter, Paul (University of Adelaide Press, 2014)
In 2011, Professor Adrian J Bradbrook retired from a distinguished scholarly career spanning over forty years. During this time, he made a significant contribution to teaching and scholarship not only in property law - specifically to leasehold tenancies law and easements and restrictive covenants - but also to energy law, especially the emerging and growing field of solar energy. This book brings together those people who worked closely with Bradbrook, each an expert in their own right, to honour a career by critically engaging with the contributions Bradbrook made to property and energy law. Each author has chosen a topic that both fits with their own cutting-edge research and explores the related contributions made by Bradbrook. Most unusually, this collection ranges widely across property law, energy law and human rights.